1996
DOI: 10.1097/00007890-199609270-00005
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Hyperacute Rejection by Human Decay Accelerating Factor in Xenogeneic Perfused Working Hearts

Abstract: As a potential source of organs for xenotransplantation, pigs that are transgenic for human decay accelerating factor (DAF) have been bred in order to overcome hyperacute rejection. We investigated the protective effect of human DAF in a porcine working heart model perfused by human blood. Hearts of normal landrace pits served as controls. The following parameters were measured: stroke work index, coronary flow and arteriovenous oxygen consumption, 6-keto prostaglandin F1alpha and prostaglandin E2 as markers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 9 publications
1
22
1
Order By: Relevance
“…These proteins inhibit steps in the complement cascade, and although the natural antibodies will still be bound to the ␣-Gal antigen, cell lysis would be prevented. Several transgenic pig herds have been developed expressing one (e.g., CD55 [104]) or more genes encoding human complement-regulatory proteins.…”
Section: Genetically Engineered Pigsmentioning
confidence: 99%
“…These proteins inhibit steps in the complement cascade, and although the natural antibodies will still be bound to the ␣-Gal antigen, cell lysis would be prevented. Several transgenic pig herds have been developed expressing one (e.g., CD55 [104]) or more genes encoding human complement-regulatory proteins.…”
Section: Genetically Engineered Pigsmentioning
confidence: 99%
“…Further, a recent study on the activity of IL-6 in the differentiation of monocytes to macrophages and dendritic cells has shown that IL-6 inhibits the differentiation of monocytes to dendritic cells by promoting their differentiation toward macrophages [25]. In addition, IL-6 has been used as a marker of mononuclear cell activation in a recent study investigating the protective effect of human decay accelerating factor in a porcine hearts perfused by human blood [40].…”
Section: > Imentioning
confidence: 99%
“…In the same time, numerous extracorporeal models and a working heart device were developed in order to investigate HAR and the immunological reactions also in transgenic pig hearts [113]. The transplantation of h-DAF transgenic pig hearts to the abdominal aorta of cynomolgus monkeys resulted in a beating time of up to 62 days, mean 42 days [65].…”
Section: Xenogenic Heart Transplantationmentioning
confidence: 99%